Single-polymer composites based on polylactide continuous core-sheath bicomponent fibers - Boris Marx; Lars Bostan; Andrea Miene; David May (Polymer Testing)
Biopolymers offer a potential solution to the challenges posed by conventional plastics in terms of resource conservation and environmental protection. One area of application is the use of biopolymers in single polymer composite (SPC) materials. This paper describes the formation of a Polylactide (PLA) SPC using continuous bicomponent fibers which allows to realize a high fiber volume content (φ) of 75 %. The sheath of the fiber is made of amorphous PLA, while the core is made of semi-crystalline PLA. After consolidating the continuous bicomponent fiber into SPC, the amorphous PLA provides the matrix while the semi-crystalline PLA serves as reinforcement. The mechanical testing in fiber direction of the PLA-SPC resulted in a tensile strength of 107.5 ± 2.2 MPa and a Young's modulus of 9.7 ± 0.6 GPa. Differential scanning calorimetry (DSC) revealed two melting points for amorphous PLA (141.1 ± 0.2 °C) and semi-crystalline PLA (178.2 ± 0.9 °C). The SPC developed from PLA continuous bicomponent fibers shows a significantly higher Young's modulus compared to other PLA-SPC that is comparable to polyethylene terephthalate (PET) SPC.